"Trying to be everything else": Examining the challenges experienced by youth development workers. (October 2021) - Bloomer, Rebecka; Brown, Aishia A.; Winters, Andrew M.; Domiray, Anna
Highlights: The youth development workforce is largely unexplored within the literature. Using a constructivist grounded theory methodology, challenges of youth workers were explored. Job role clarity, emotional exhaustion, and youth behavior emerged as primary challenges. Organizations need to support youth workers by clearly defining their role. Organizations should identify areas where additional capacity and support are needed. Abstract: Youth development research and practice have evolved significantly in the last forty years, as theoretical orientations shifted to reflect the focus on youth strengths and assets. While research on youth development has evolved, research with an emphasis on those who work with youth in this context is strikingly limited. This study aimed to bridge this research gap by using a constructivist grounded theory approach to explore the challenges experienced by youth development workers. Semi-structured, in-depth qualitative interviews were used to garner perceptions of challenges. Nineteen participants completed a total of 26 interviews. Participants explained the complex and intertwining relationship of internal and external challenges they experienced. Participants grounded these challenges within the context of their work environment. Their shared meaning across these topics informed the development of a context specific framework including three themes of (a) "trying to be everything else" (b) emotional response and (c) youth behavior, with a subtheme of (d) youth behavioral health. The field of youth development often focuses on building more professional development opportunities however, results from this study show a need to address challenges youth workers experience within the bounds of the youth program and larger organization. Specifically, there is a need for organizations to support youth workers by clearly defining their role, and identifying areas where additional capacity and support are needed.